Perioperative Inotrope Therapy and Atrial Fibrillation Following Coronary Artery Bypass Graft Surgery: Evidence of a Racial Disparity. Issue 3 (3rd February 2017) - Efird, Jimmy T.; Kiser, Andy C.; Crane, Patricia B.; Landrine, Hope; Kindell, Linda C.; Nelson, Margaret‐Ann; Jindal, Charulata; Sarpong, Daniel F.; Griffin, William F.; Ferguson, T. Bruce; Chitwood, W. Randolph; Davies, Stephen W.; et al.
Abstract : Background and Objective: Following coronary artery bypass graft (CABG) surgery, mortality rates are significantly higher among black patients who experience postoperative atrial fibrillation (POAF). Perioperative inotropic therapy (PINOT) was associated with POAF in previous reports, but the extent to which race influences this association is unknown. In the present study, the relationship between PINOT, race, and POAF was examined in patients undergoing CABG surgery. Methods and Setting: Clinical records were examined from a prospectively maintained cohort of 11, 855 patients (median age 64 yrs; 70% male; 16% black) undergoing primary isolated CABG at a large cardiovascular institute in the southeastern region of the United States. Relative risk (RR) and 95% confidence intervals (CIs) were computed using log‐binomial regression. Main Results: The association between PINOT and POAF was significantly increased among black patients (adjusted RR 1.7, CI 1.4–2.0) compared with white patients (adjusted RR 1.3, CI 1.2–1.4) (pinteraction = 0.013). Conclusions: These findings suggest that PINOT may be disproportionately associated with POAF among black patients undergoing CABG surgery. Additional studies are needed to examine further the potential underlying mechanisms of this association.